Including and Serving Students With Special Needs in Catholic Schools: A Report of Practices - Durow, W. Patrick (Catholic Education: A Journal of Inquiry and Practice, 2007)
Based on responses to a survey of 19 Midwestern Catholic dioceses, the author reports the mission, educational practice, and financial means utilized to serve students with special needs in Catholic schools.